Revealing the dynamics of a local Alpine windstorm using large-eddy simulations - N. Krieger; H. Wernli; M. Sprenger; C. Kühnlein (Weather and Climate Dynamics)
The local atmospheric flow in mountainous terrain can be highly complex and deviate considerably from the ambient conditions. One example is a notorious local windstorm in a narrow and deep valley in northeastern Switzerland, known as the Laseyer, that had previously even caused a train derailment. This windstorm is characterized by strong southeasterly winds blowing perpendicular to the valley axis during strong northwesterly ambient flow conditions. We investigate the mechanism of this local windstorm and its sensitivity to changes in the prescribed ambient wind using large-eddy simulation (LES). The LESs are performed at a horizontal grid spacing of 30 m and by applying a terrain-following vertical coordinate with steep slopes of the real topography reaching nearly 80°. The simulations, driven by strong northwesterly ambient winds, successfully capture the flow reversal in the valley with quasi-periodically occurring short episodes of wind bursts regularly exceeding 20 m s−1 and in exceptional cases exceeding 35 m s−1. The flow reversal is explained by an amplifying interplay of (1) a recirculation region formed by flow separation in the lee of the upstream ridge and (2) a vortex caused by a positive pressure anomaly formed by the northwesterly winds impinging on the downstream mountain. This formation mechanism is supported by a simulation in which the height of the downstream mountain is reduced, resulting in a decrease in the strength of the reversed in-valley flow. In agreement with previous observational studies, a series of simulations with modified ambient wind conditions reveal that the intense gusts (>20<mspace width="0.125em" linebreak="nobreak"/>m<mspace linebreak="nobreak" width="0.125em"/>s-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="f13711aaa6f8f424fd821418ed88857d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wcd-6-447-2025-ie00001.svg" width="52pt" height="13pt" src="wcd-6-447-2025-ie00001.png"/></svg:svg>) only occur in a narrow window of ambient wind directions and if its speed is at least 16 m s−1. Smoothing the topography in the LESs reduces the maximum wind speeds in the target region by 10 %–30 %. Overall, our semi-idealized LESs in complex and steep terrain reveal the three-dimensional structure and the mechanism of the local windstorm. Moreover, they point to the importance of the local topography and its complex interplay with the three-dimensional and transient flow leading to the in-valley flow reversal and strong winds that characterize the Laseyer. The study further highlights the importance of the topographic details for the quantitatively correct simulation of atmospheric flows in complex terrain.